2019
DOI: 10.1136/jech-2019-212474
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and oral microbiota in low-income and African-American populations

Abstract: BackgroundCigarette smoking is a common risk factor for diseases and cancers. Oral microbiota is also associated with diseases and cancers. However, little is known about the impact of cigarette smoking on the oral microbiota, especially among ethnic minority populations.MethodsWe investigated cigarette smoking in relationship with the oral microbiota in a large population of predominately low-income and African-American participants. Mouth rinse samples were collected from 1616 participants within the Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
5
25
0
Order By: Relevance
“…Furthermore, by comparing the within- and between-group distances, the never and former smokers turned out to be more alike than the current smokers, who appeared to be a more heterogeneous group, suggesting that smoking-related changes are not permanent and the bacteria depleted by cigarette smoking could be restored after quitting smoking. Similar results were obtained by Yang et al [ 32 ], who conducted a study on a large population of predominately low-income and African-American participants, including 592 current smokers, 477 former smokers, and 547 never-smokers. The authors, considering that the oral microbial composition of current smokers differed from former and never-smokers and that such differences were not observed between former smokers and never-smokers, concluded that the changes caused by the strong impact of smoking on oral microbial composition may be recovered after smoking cessation.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, by comparing the within- and between-group distances, the never and former smokers turned out to be more alike than the current smokers, who appeared to be a more heterogeneous group, suggesting that smoking-related changes are not permanent and the bacteria depleted by cigarette smoking could be restored after quitting smoking. Similar results were obtained by Yang et al [ 32 ], who conducted a study on a large population of predominately low-income and African-American participants, including 592 current smokers, 477 former smokers, and 547 never-smokers. The authors, considering that the oral microbial composition of current smokers differed from former and never-smokers and that such differences were not observed between former smokers and never-smokers, concluded that the changes caused by the strong impact of smoking on oral microbial composition may be recovered after smoking cessation.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, smoking contributes to the alteration in the oxygen tension of the oral and upper gastrointestinal microenvironment that encourages persistence of microaerophilic bacteria replacing the commensal beneficial species [ 12 , 13 ]. Previous studies have shown an increased prevalence of the genera Atopobium , Campylobacter , and Prevotella among smokers and selective depletion of certain phyla, including Proteobacteria [ 12 , 14 16 ]. Thus, tobacco smoking creates a unique dysbiotic environment in the oral cavity, influencing the microbiota composition with far-reaching consequences in the local and systemic health of the host [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is important in view of the increasing evidence indicating that compositional and functional disturbances in the oral microbiome (dysbiosis) may play a role in oral cancer [7,8]. In fact, few recent studies have shown that current smokers have a significantly altered oral microbiome compared to non-or former smokers [9,10], Furthermore, in a Syrian Golden hamster cheek pouch carcinogenesis model, 4-week application of ST was shown to significantly disrupted the oral microbiota [11]. How ST products affect the human oral microbiome, and whether that may play a role in their carcinogenicity has not been studied.…”
Section: Introductionmentioning
confidence: 99%